Government Investment Credit Programs and Local Own Source Revenue: A Literature Review of The Kredit Kukar Idaman Case In Kutai Kartanegara Indonesia - Zam Zam Fu’adain; Eny Rochaida; Emmilya Umma Aziza Gaffar (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
This article reviews literature on how local government investment and public credit programs contribute to local own-source revenue (PAD), using Kredit Kukar Idaman in Kutai Kartanegara as a contextual case. The review shows that public investment can improve infrastructure, productivity, and business expansion, while credit programs can ease SME liquidity constraints and support market participation. However, their fiscal effects on PAD are indirect and depend on implementation quality, financial literacy, institutional coordination, and tax administration. The article argues that these policies are most effective when directed to productive sectors, supported by mentoring, and integrated with local revenue management. Overall, the literature suggests that local credit programs should be treated as part of a broader development strategy linking economic growth with fiscal sustainability. This article reviews the literature on how local government investment and public credit programs contribute to local own-source revenue (Pendapatan Asli Daerah, PAD), using the Kredit Kukar Idaman program in Kutai Kartanegara as a contextual case. The review finds that government investment can strengthen local economic capacity through infrastructure, productivity gains, and business expansion, while credit programs can improve SME liquidity, production, and market participation. However, the literature also shows that the fiscal impact on PAD is indirect and depends on implementation quality, financial literacy, institutional coordination, and tax administration effectiveness. The article concludes that investment and credit policies are most likely to raise PAD when they are linked to productive sectors, accompanied by mentoring, and supported by a strong local revenue system.